Budidaya Sayuran Melalui Sistem Vertikultur Sebagai Solusi Untuk Pemanfaatan Lahan Sempit Di Kelurahan Medokan Ayu Kota Surabaya (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Medokan Ayu Village is 3 km from the UPN "Veteran" East Java campus. The location of this service is located in Griya Amerta Housing RW 15, Medokan Ayu Village. Like housing in general, residential land area is usually relatively small, has relatively narrow yards and the distance between houses is also close to each other. So that the area of ​​the yard owned by the community for cultivating crops while developing agriculture is not very supportive. Verticulture or what can be called vertical farming is a system of cultivating plants vertically, so that the planting medium is put in a container that stands and rises up. This cultivation technique can be used in two ways, namely with water and soil as the planting medium. Pakcoy can be harvested when it is 40-50 days old, while curly lettuce can be harvested when it is 40-60 days old. This verticulture cultivation uses a mixture of several planting media such as soil, cocopeat, roasted husks, and kohe. The goal is for the plants to meet their nutritional needs and nutrients, so that the plants can grow optimally and have good quality.